Income sources and intergenerational transfers in different regimes: The case of East Germany's transformation - Fanny Annemarie Kluge; Tobias Vogt (Demographic Research, 2015)
Background: Intergenerational transfers are a fundamental feature of the economic life cycle. In western welfare states, private transfers typically flow from members of the older generations to their children and grandchildren, especially when in need, while public transfers tend to flow in the opposite direction. Objective: This paper shows the changes in the relative importance of various income sources, such as labor income and public and private transfers, among eastern Germans of different age groups from 1988 to 2008. This period of rapid societal transition represents a quasinatural experiment setting that allows us to study how different political regimes shape the patterns of income and transfers among different age groups. Methods: To study the income and transfer patterns among different age groups, we use the National Transfer Accounts method and rarely used data sources, such as the income survey of blue-collar and white-collar worker households conducted in 1988 in the German Democratic Republic (GDR). Results: We find that there was a shift in income and transfer patterns immediately after the fall of the Berlin Wall. We show that the elderly gained the most from reunification, and transferred an increasing fraction of their income to their children and grandchildren.